P2R - A Pairwise Testing Strategy Supporting Execution Resumption - Helal, Mohammed H.S.; Kamal Z., Zamli (2012)
Pairwise strategies have been proven to be useful to systematically sample test data for interaction testing consideration. However, generating pairwise test suite can be a painstakingly difficult endeavor especially involving large configurations. Here, the generation process can take hours and even days to complete owing to the need to sample from large numbers of input parameters and values. In the case of interruption (e.g. due to power failure or hardware malfunctions), there is often a need to restart the whole generation process again from the beginning. If the pairwise test suite is significantly large and the overall progress is near completion, restarting means a lot of wasted efforts.In order to address the aforementioned issues, we have developed a new pairwise strategy, called P2R, which can generate sufficiently competitive pairwise test suite. Unlike existing pairwise strategies, P2R also has the capability to seamlessly resume existing test generationprocess upon interruption.